Estimating chemical ecotoxicity in EU ecolabel and in EU product environmental footprint. (September 2018) - Saouter, Erwan; De Schryver, An; Pant, Rana; Sala, Serenella
Abstract: The EU Commission Ecolabel and the Product and Environmental Footprint (PEF) aim at promoting the development and consumption of greener products. The product aquatic toxicity score from these 2 methods may lead in some circumstances to opposite conclusions. Although this could be interpreted as an inconsistency, the score should not be compared to each other but used in a complementary way. In short, CDV provided a "full" product formula aquatic toxicity score, even if some chemicals may never reach or persist in freshwater ecosystems. The USEtox® score, by integrating fate and exposure, focuses on the potential toxicity of persistent-water-soluble chemicals at steady state. Since no risk or safety assessment can be conducted with USEtox® nor with the CDV, both are a hazard-based scoring system. This short communication clarifies the difference between approaches underpinning the toxicity scores used in Ecolabel and PEF, providing guidance on how to interpret the results. Graphical abstract: Highlights: The outcomes of the CDV and IS could lead to different scores Both approaches have a value as they answer different questions CDV is focusing on chemicals in product with direct emission perspectives IS is focusing on persistent-water-soluble chemicals at steady state.